The Analysis of Derivational Morphemes Found in David Googins on Huberman - I Made Aditya Laras; I Komang Sulatra (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study investigates the use of derivational morphemes in David Goggins' motivational speech, “12 Minutes to Change Your Life,” featured on Huberman's podcast. Derivational morphemes, which create new words and alter grammatical categories, are essential in understanding language development and communication. Despite extensive research on derivational morphemes in various texts, there is limited analysis of their usage in motivational speeches. This study addresses this gap by analyzing Goggins' speech, focusing on identifying and classifying derivational morphemes. Using qualitative methods, the speech was transcribed, and words containing derivational morphemes were analyzed based on the theories of Fromkin, Rodman, and Hyams (2011). The findings reveal 23 instances of derivational morphemes, divided into class-changing and class-maintaining categories. Notable transformations include adjectives to adverbs, verbs to nouns, and adjectives to nouns, with the most frequent being adjectives to adverbs. The study provides insights into the function and impact of derivational morphemes in spoken motivational content, contributing to the broader understanding of morphology in language use.